Clove flower extracts (Syzgium aromaticum) increased incision wound epithelization, platelet count, and TGF-β levels in methicillin-resistant Staphylococcus aureus-infected rats - Wibowo, Suryo; Lestari, Endang Sri; Arifin, Muhammad Thohar; Prajoko, Yan Wisnu; Susilaningsih, Neni (JKKI : Jurnal Kedokteran dan Kesehatan Indonesia, 2023)
Background: The wound healing process consists of three phases, namely inflammation, proliferation, and remodeling. Many cells and mediators are involved in this process, including platelets and transforming growth factor-β (TGF-β). Methicillin-resistant Staphylococcus aureus (MRSA) is a bacterial strain resistant to beta-lactam antibiotics. Clove flower (Syzygium aromaticum) is an herb with properties to promote wound healing Objective: To determine the effect of clove flower extract on increasing epithelialization of incision wounds, platelet counts, and TGF-β levels in mice infected with MRSA Methods: A randomized experimental study on 30 male wistar rats (Rattus norvegicus) infected with MRSA. All rats were randomly divided into six groups; healthy control, positive control induced by MRSA and Vancomycin 9 mg/200 gram body weight (gbw), negative control MRSA with normal saline, and administration of clove flower extract (CFE) 25 mg/200 gbw, CFE 50 mg/200 gbw, and CFE 100 mg/200 gbw. Examination of the sectioned wound epithelium was performed histologically using Hematoxylin-Eosin (HE), while platelet count and TGF-β levels were measured using an ELISA RAB0479 kit simultaneously on the 21st day. Results: Histological examination of rats treated with CFE 100 mg/200 gbw and uninfected rats showed complete epithelization. Platelet counts and TGF-β levels were significantly higher in rats administered CFE 100 mg/200 gbw (p<0.001) compared to the other five groups. Conclusion: Administrating CFE increased incision wound epithelialization, platelet count, and TGF-β levels in MRSA-infected rats.